2022
DOI: 10.1155/2022/8598046
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of 9 Gene Signatures by WGCNA to Predict Prognosis for Colon Adenocarcinoma

Abstract: Background. A risk assessment model for prognostic prediction of colon adenocarcinoma (COAD) was established based on weighted gene co-expression network analysis (WGCNA). Methods. From the Cancer Genome Atlas (TCGA) database, RNA-seq data and clinical data of COAD patients were retrieved. After screening of differentially expressed genes (DEGs), WGCNA was performed to identify gene modules and screen those associated with COAD progression. Then, via protein-protein interaction (PPI) network construction of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Studies using this weighted co-expression network approach in the open-field blast setting have not been reported as of yet. Weighted co-expression network analysis has been used to predict prognosis in patients with colorectal adenocarcinoma and glioblastoma [ 55 , 56 ], to identify key genes related to HBV-associated hepatocellular carcinoma [ 57 ], and to classify individual humans into TBI or control groups based on WGCNA results [ 58 ]. Using this approach, we identified a key phosphopeptide module (turquoise module) that predicted learning index ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using this weighted co-expression network approach in the open-field blast setting have not been reported as of yet. Weighted co-expression network analysis has been used to predict prognosis in patients with colorectal adenocarcinoma and glioblastoma [ 55 , 56 ], to identify key genes related to HBV-associated hepatocellular carcinoma [ 57 ], and to classify individual humans into TBI or control groups based on WGCNA results [ 58 ]. Using this approach, we identified a key phosphopeptide module (turquoise module) that predicted learning index ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of signature early symptoms, most patients are already metastatic when diagnosed, which leads to a lower 5-year survival rate of only 14% even with systemic therapy ( Siegel et al, 2022 ). As the existing prognostic indicators for COAD cannot reveal its biological heterogeneity, it is crucial to tap more accurate predictive tools that can combine clinicopathological and molecular characteristics ( Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the metabolic, protein interaction, and gene expression networks in biological environment fit in a scale-free topological distribution [ 25 ]. Genes are clustered in the form of a coexpression network, in which the ones connected with more genes are in the core position in modules with high modular identity, which are called hub genes [ 26 , 27 ]. In previous studies, they have been distinguished by the gene expression difference of samples subjected to differential expression analysis alone [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%